Optimizing the Role of the Thematic Real Work Lecture (KKN-T) Students as Lecturers in Improving Education in Jambugeulis Village, Kuningan Regency, West Java - Pratomo, Herdianto Wahyu; Ghifari, Moch. Adam; Az-Zahraa3, Delia (PT FORMOSA CENDEKIA GLOBAL, 2024)
To implement education, a teaching staff is needed whose duty is to provide teaching, both in formal and non-formal educational institutions. The purpose of the KKN-T program in this village is to provide community service and contribute to improving the education of children in the village. The level of enthusiasm of children in Jambugeulis village is very high; however, the number of teaching staff available in the village is very limited, which is an obstacle for children to get the education they need. Findings from KKN-T activities provide an overview of the spirit and enthusiasm shown by children and the community towards the role of students as teachers in helping education in Jambugeulis village through formal and non-formal education activities that have been implemented by KKN-T Majalengka University.